2021
DOI: 10.4136/ambi-agua.2780
|View full text |Cite
|
Sign up to set email alerts
|

Saline waters and nitrogen/potassium fertilization combinations on physiological aspects and production of West Indian cherry

Abstract: This study evaluated the influence of combinations of nitrogen and potassium doses on the physiology and fruit production of West Indian cherry irrigated with waters of different salinities in the second year of cultivation. The experiment was conducted in the municipality of Pombal-PB, Brazil, in plastic containers adapted as lysimeters installed in the field, in a randomized block design, 5 x 4 factorial scheme corresponding to five levels of electrical conductivity of irrigation water (ECw): 0.3, 1.3, 2.3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Similar results were obtained in the research developed by Silva et al (2021), when they evaluated the photosynthetic pigments of West Indian cherry under salt stress (ECw ranging from 0.3 to 4.3 dS m -1 ). The authors observed a reduction of 35.68% in plants irrigated with the ECw of 4.3 dS m -1 in comparison to those grown under the ECw of 0.3 dS m -1 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were obtained in the research developed by Silva et al (2021), when they evaluated the photosynthetic pigments of West Indian cherry under salt stress (ECw ranging from 0.3 to 4.3 dS m -1 ). The authors observed a reduction of 35.68% in plants irrigated with the ECw of 4.3 dS m -1 in comparison to those grown under the ECw of 0.3 dS m -1 .…”
Section: Resultssupporting
confidence: 87%
“…Photosynthetic pigments and quantum yield of West Indian cherry under salt stress Overall, NPK combinations FC3, FC4, and FC6 improved the utilization of available energy, highlighting the importance of these nutrients through adequate combinations for physiological activities, as reported by Silva et al (2021).…”
Section: Source Of Variation Glmentioning
confidence: 71%
“…The treatment with the highest N and K levels resulted in the lowest values for this variable, which may indicate an increase in substrate salinity due to the increase in urea and K 2 O combined with salt accumulation resulting from the application of irrigation water. Excess salt leads to greater energy use for osmotic adjustment, decreasing the amount of energy substrate applied for plant growth (SILVA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In northeastern Brazil, West Indian cherry cultivation has proven to be an economically important activity for the region, especially in its semi-arid portion, due to the species' adaptation to the local edaphoclimatic conditions [4,5]. However, it is known that the semiarid region of Brazil is characterized, among other factors, by frequent water restrictions imposed by drought events, high evapotranspiration rates, and groundwater sources with high salt concentrations [6].…”
Section: Introductionmentioning
confidence: 99%